Synthesis and Characterization of Molecularly Imprinted Polymer for the Removal/Extraction of Thymol from Spiked Blood Serum and River water - Bhawani, Showkat Ahmad; Salma, Bakhtiar; Syed Rizwan, Shafqat (Asian Publication Corporation, 2019)
Molecularly imprinted polymers (MIPs) were prepared by precipitation polymerization using thymol as a template molecule, acrylamide as a functional monomer and N,N-methylbisacrylamide as the crosslinker with a non-covalent approach. The polymers were characterized by scanning electron microscopy (SEM), energy-dispersive X-ray spectroscopy (EDX), fourier-transform infra red spectroscopy(FT-IR) and Brunauer-Emmett-Teller (BET). The SEM results depicted that the shape of polymer particles is spherical with uniform size (micrometers). The BET results also showed better surface area, pore size and pore volume of MIP as compared to non-imprinted polymer (NIP). A series of parameters such as initial concentration, polymer dosage, effect of pH and slectivity with structural analogue were conducted. The selectivity of MIP towards thymol was appreciable as compared to its structural analogue gallic acid with a relative selectivity coefficient of 3.59. Finally, MIP has been successfully used for extraction of thymol from the spiked blood serum (84 %) and river water sample (98 %).